Прагматична філогенетична класифікація спорових судинних рослин флори України - Мосякін, С.Л.; Тищенко, О.В. (Український ботанічний журнал, 2010)
Предложен вариант прагматической классификационной схемы споровых сосудистых растений флоры Украины в составе 4 отделов (Lycopodiophyta, Psilotophyta, Equisetophyta, Po ly podiophyta), 5 классов (Lycopodiopsida, Isoëtopsida, Ophioglossopsida, Equisetopsida, Poly podiopsida), 7 порядков и 19 семейств. Для каждого семейства приведены роды и количество видов, которые представлены на территории Украины. Схема учитывает современную интерпретацию морфологических и молекулярно-филогенетических данных о филогении споровых растений, традиции украинской и российской систематики и включает ряд пересмотров места и объема отдельных таксонов. Схему предлагается использовать в новом издании «Флоры Украины», а также в отечественных учебниках и учебных пособиях. A variant of a pragmatic classification scheme is proposed for vascular crypytogamic plants of the flora of Ukraine. The scheme includes 4 divisions (Lycopodiophyta, Psilotophyta, Equisetophyta, Poly podiophyta), 5 classes (Lycopodiopsida, Isoëtopsida, Ophioglossopsida, Equisetopsida, Polypodiopsida), 7 orders and 19 families. For each family, genera occurring in Ukraine are listed, with the number of species indicated for each genus. The clasification scheme is bases on modern interpretation of morphological and molecular phylogenetic data on vascular cryptogamic plants, takes into consideration traditions of Ukrainian and Russian taxonomic schools, and includes some adjustments of positions and circumscriptions of some taxa. This classification is proposed to be used in the new edition of the Flora of Ukraine, as well as in new Ukrainian manuals and reference books.